Formalism for chaotic behavior of the bunched beam - Parsa, Z.; Zadorozhny, V. (Вопросы атомной науки и техники, 2001)
Using Cesaro mid of Fourier series the quasi-linear Vlasov’s equation is transformed to the integral Fredholm equation. New results on the oscillatory behavior of solution are obtained. An extension to perturbing equation is also included.